Effect of luteal-phase GnRH agonist on frozen-thawed embryo transfer during artificial cycles: a randomised clinical pilot study - Liu, Yanghong; Huang, Kaishu; Chen, Cheng; Wen, Li; Lei, Min; Guo, Yabin; Tang, Bin (Frontiers in Endocrinology, 2023)
Purpose: This randomised clinical pilot study evaluated the effect of the mid-luteal additional single dose of gonadotropin-releasing hormone agonist (GnRH-a) on the clinical outcome of the females subjected to artificial cycle frozen-thawed embryo transfer (AC-FET). Methods: A total of 129 females were randomised into two groups (70 in the control group and 59 in the intervention group). Both groups received standard luteal support. The intervention group was given an extra dose of 0.1 mg GnRH-a in the luteal phase. The live birth rate served as the primary endpoint. The secondary endpoints were the positivity of pregnancy tests, the clinical pregnancy rate, the miscarriage rate, the implantation rate, and the multiple pregnancy rate. Results: There were more positive pregnancy tests, clinical pregnancies, live births, and twinning pregnancies, and fewer miscarriages observed in the intervention arm compared to the controls, though no statistical significance was concluded. No difference was found in the number of macrosomia in the two groups. There was no congenital abnormality newborn. Conclusions: Overall, the difference of 12.1 percentage points in the live births rate (40.7% vs 28.6%) between the two groups, however, is statistically insignificant. the improvement of the pregnancy outcome supports the non-inferiority of GnRH-a added during the luteal phase in AC-FET. Larger-scale clinical trials are required to further establish the positive benefits.